Characterization of Stabilised Sewage Sludge for Reuse in Road Pavement - Medaoud, Saber; Mokrani, Larbi; Mezhoud, Samy; Ziane, Sami (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In recent years, the disposal of sewage sludge has been a major concern worldwide because of their potential treat in relation with the contamination of ground water and food chain. Furthermore, their poor mechanical properties don`t allow a possible direct use in civil engineering applications. For these reasons, it was important to explore more opportunity to reuse this by-product of sewage treatment. In this frame, the solidification-stabilisation technique (S-S) which is based on hydraulic binders can improve the properties of sewage sludge so that it can be used in civil engineering application, especially in road pavements.
Keywords: sewage sludge; hydraulic binders; road pavements; geotechnical properties; osad ściekowy; spoiwa hydrauliczne; chodniki drogowe; właściwości geotechniczne